2010
DOI: 10.1021/tx1001332
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Fate of a Sulfenic Acid Intermediate in the Metabolic Activation of the Antithrombotic Prodrug Prasugrel

Abstract: Metabolic activation of the tetrahydro-thienopyridine antithrombotic prodrug, prasugrel, involves two steps: an esterase-dependent hydrolysis of its acetate function leading to thiolactone 6 and a cytochrome P450 (P450)-catalyzed oxidative cleavage of this thiolactone. This article shows that this second step involves the intermediate formation of a sulfenic acid 9 that has been trapped by dimedone during the metabolism of prasugrel by rat and human liver microsomes. The dimedone adduct has been characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…Thiolactone 2 (a 1:1 mixture of 2a and 2b) was incubated for 15 minutes at 37°C with HLMs in the presence of NADPH and GSH (5 mM) to reduce sulfenic acid 4 to the corresponding thiols (H1-H4) (Dansette et al, 2009(Dansette et al, , 2010Zhang et al, 2013). A UPLC-Q/TOF MS study of the incubate showed the formation of four thiol isomers exhibiting a molecular ion (ESI + ) corresponding to [M + H] + that was characterized by two peaks at m/z = 356.073 and 358.071 with the ratio expected for the 35 Cl and 37 Cl isotopes.…”
Section: Chiral Stability Of Thiolactone 2 Isomers (2a and 2b) In Bufmentioning
confidence: 99%
“…Thiolactone 2 (a 1:1 mixture of 2a and 2b) was incubated for 15 minutes at 37°C with HLMs in the presence of NADPH and GSH (5 mM) to reduce sulfenic acid 4 to the corresponding thiols (H1-H4) (Dansette et al, 2009(Dansette et al, , 2010Zhang et al, 2013). A UPLC-Q/TOF MS study of the incubate showed the formation of four thiol isomers exhibiting a molecular ion (ESI + ) corresponding to [M + H] + that was characterized by two peaks at m/z = 356.073 and 358.071 with the ratio expected for the 35 Cl and 37 Cl isotopes.…”
Section: Chiral Stability Of Thiolactone 2 Isomers (2a and 2b) In Bufmentioning
confidence: 99%
“…Conversion of this intermediate to the ring opened carboxy thiol product requires a P450 oxidation to cleave the ring and give a carboxy sulfenic acid product that is reductively converted to the pharmacologically active thiol drug [85]. The sulfenic acid can be chemically trapped [8587]. As reported for clopidogrel, thioesterase opening of the thiolactone yields a thiol derivative with the double bond at a different ring position.…”
Section: Prodrugs For Other Indicationsmentioning
confidence: 99%
“…It is well documented that P450-mediated bioactivation involves two consecutive oxidative steps (Dansette et al, 2010(Dansette et al, , 2012a; clopidogrel is first monoxygenated to 2-oxoclopidogrel, which is, in turn, oxidized to the AM in the second step. Although it has been argued that esterase PON1 is responsible for converting 2-oxoclopidogrel to the AM (Bouman et al, 2011), increasing evidence supports the idea that 2-oxoclopidogrel is converted to the AM via a sulfenic acid intermediate (Dansette et al, 2009(Dansette et al, , 2010(Dansette et al, , 2012a, as illustrated in Scheme 1. According to Scheme 1, 2-oxoclopidogrel is first oxidized to a sulfenic acid intermediate by P450s.…”
Section: Introductionmentioning
confidence: 99%